GLOBAL PROBLEMS (Modern education and development, 2025)
This article analyzes the current global problems of modern world. Climate change is covered by issues such as climate change, environmental problems, demographic problems, poverty and social problems, terrorism and technological risks. The reasons for these problems are discussed on humanity and the potential solutions. The role of international organizations and governments in addressing these problems will be considered. The article includes a comprehensive approach to global problems and suggestions for their elimination.